Molecular dynamics study in the Ce0.9M0.1O1.95 (M=Gd, Sm) doped and co-doped CeO2 systems: Structure and oxygen diffusion. Issue 17 (1st December 2019) - Vives, S.; Ramel, D.; Meunier, C.
Abstract: Doped ceria is known for its high ionic conductivity which is limited by the creation of defect clusters. We investigate using Molecular Dynamics the evolution of the structure and oxygen diffusivity of the Ce0.9 M0.1 O1.95 (M = Gd, Sm) doped and co-doped CeO2 systems. Two configurations concerning the introduction of the doping ions and oxygen vacancies inside the structure are generated and compared, the random one (R) and the neighbor one (N). The pair potential parameter set is chosen among three sets by comparison with experimental data. The pair correlation function first peak is fitted by a lognormal function to take into account the asymmetry. The evolution of the coefficient of thermal expansion, the coordination number and the bond lengths of the different ion pairs with the temperature, is presented. The influence of the local C-type sesquioxide M2 O3 structure on those parameters is discussed. No significant positive co-doping effect on the oxygen diffusion process is revealed. The random configuration of the defects leads to the highest oxygen diffusivity and to the lower activation energy whatever the doping ion (Gd, Sm or Gd/Sm).